Carbon footprint reduction practices in the Olympic Games: a policy mobility approach - Wesselia Isa Ngoenha (Current Issues in Sport Science)
Introduction The environmental impact of mega-events like the Olympic Games and the FIFA Men's World Cup has been widely criticized due to their significant contribution to greenhouse gas emissions, largely driven by infrastructure construction and resource use, and travel. Despite sustainability initiatives introduced by the IOC since the 1990s, including the 2017 "Sustainability Strategy," research indicates that these efforts rarely lead to tangible results, with environmental scores of the Games declining over time (Müller et al., 2021). Policies such as Agenda 2020 are mostly seen as recommendations, not obligations, contributing to accusations of greenwashing and unmet environmental commitments. The lack of a standardized framework for assessing and mitigating environmental impacts highlights the gap between promises and outcomes, suggesting that current approaches are insufficient to align mega-events with sustainability goals (Collins et al., 2009; Gaffney, 2013). This research thesis examines this gap to understand the ineffectiveness of these policies and their evolution over time using the policy mobility methodology, which allows us to understand how policies are created, transferred and reapplied in a new context, thanks to tools and people who transport knowledge from one place to another. The research highlights the evolution of environmental policy in the Olympic Games, tracing its origins from global environmental movements to its integration within the framework of the International Olympic Committee.